Unraveling the impact of Lactobacillus spp. and other urinary microorganisms on the efficacy of mirabegron in female patients with overactive bladder - Zhou, Zhipeng; Qiu, Yifeng; Li, Kun; Sun, Qi; Xie, Ming; Huang, Pengcheng; Yu, Yao; Wang, Benlin; Xue, Jingwen; Zhu, Zhangrui; Feng, Zhengyuan; Zhao, Jie; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Overactive bladder (OAB) is a disease that seriously affects the quality of life and mental health of patients. More and more researchers are looking at the relationship between OAB treatment and urinary microecology. In this study, we sought to determine whether differences in efficacy were related to differences in flora populations and whether specific genera were responsible for these differences, and machine learning algorithms to construct predictive models for urine flora-based treatment of OAB.Urine samples were obtained for 16S rRNA gene sequencing from a total of 64 adult female OAB patients. Patients with the Overactive Bladder Symptom Score (OABSS) were collected before and after Mirabegron treatment and divided into effective and ineffective groups. The relationship between relative abundance of microbiota and the relationship between different genera and OABSS were analyzed. Three machine learning algorithms, including Random Forest (RF), Supporting Vector Machine (SVM) and eXtreme Gradient Boosting (XGBoost) were utilized to predict the therapeutic effect of Mirabegron based on the relative abundance of genera of OAB patients.The species composition of the two groups were obviously different to some extent. The relative abundance of Lactobacillus was significantly higher in the effective group than in the ineffective group. The relative abundance of Gardnerella and Prevotella in the effective group was significantly lower than in the ineffective group. Alpha-diversity and beta-diversity were significantly different between two groups. LEfSe revealed that Lactobacillus was increased, Prevotella and Gardnerella were decreased in the effective group than the other one. Lactobacillus abundance ROC curve had high predictive accuracy. After treatment, there were negative correlations between OABSS and the abundance of Lactobacillus, whereas Prevotella and Gardnerella were opposite. In addition, RF, SVM and XGBoost models were highly prediction capacity of the Mirabegron effect in OAB patients in the test cohort.This study indicated the effect of urinary flora on the efficacy of Mirabegron and Lactobacillus might be a potential marker for evaluating the therapeutic effect based on Mirabegron in OAB patients.